URGENSI PENDIDIKAN KARAKTER BANGSA DI SEKOLAH - Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2015)
In today's era of globalization we often encountered a number of actions away from the noble values of the implementation of the objectives of education. For example quarrel between students, drunkenness that most perpetrators of students, abuse of illicit drugs, and other, even worse, not only junior and senior high school students are to be the culprit, but also elementary school students do this. That is because education is still a routine of materials stuffing to the student or transferring of knowledge. It is therefore important to implement a new educational concept, the concept of private education that emphasizes the balancing of students with cognitive, psychomotor, and affective. This concept was then widely referred to as the concept of character education. Character education should be imparted to the personal child as early as possible, especially when children are in the family circle. The role of parents is enormous in shaping the morals and attitudes of children. In the Qur'an, many verses that offend or discuss about character education, namely in the letter Al-Isra verse 23 and letter Luqman verse 14, this proves that the Qur'an pays more attention to the character building.